2019
DOI: 10.3390/ijms20010132
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Novel Functions of the Small GTPase Ypt1p under Heat-Shock by Characterizing a Temperature-Sensitive Mutant Yeast Strain, ypt1-G80D

Abstract: In our previous study, we found that Ypt1p, a Rab family small GTPase protein, exhibits a stress-driven structural and functional switch from a GTPase to a molecular chaperone, and mediates thermo tolerance in Saccharomyces cerevisiae. In the current study, we focused on the temperature-sensitive ypt1-G80D mutant, and found that the mutant cells are highly sensitive to heat-shock, due to a deficiency in the chaperone function of Ypt1pG80D. This defect results from an inability of the protein to form high molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Samples of vector, G-AtBAG2 , G-AtBAG2-Nt , G-AtBAG2-M , and G-AtBAG2-Ct transformants collected at the 60 min time point were subjected to trypan blue (TB) staining and spot assays. The TB staining assay was performed as described previously [ 16 ]. To conduct spot assays, the concentration of each culture was adjusted to an optical density (OD 600 ) of 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Samples of vector, G-AtBAG2 , G-AtBAG2-Nt , G-AtBAG2-M , and G-AtBAG2-Ct transformants collected at the 60 min time point were subjected to trypan blue (TB) staining and spot assays. The TB staining assay was performed as described previously [ 16 ]. To conduct spot assays, the concentration of each culture was adjusted to an optical density (OD 600 ) of 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…In yeast, Ypt1 plays an important role in the regulation of UPR by stabilizing unprocessed HAC1 RNA under normal growth conditions, avoiding UPR activation when there are no stress conditions [ 124 ]. In fact, Ypt1 can switch molecularly and functionally from GTPase to a molecular chaperone under heat stress conditions, enhancing the resistance of the cell under these conditions [ 125 ].…”
Section: The Role Of Rab1 In the Secretory Pathwaymentioning
confidence: 99%
“…This study demonstrated that Rab8A mediates the transport of the lipid flippase P4-ATPase from the ER to the plasma membrane. Kang et al [ 24 ] studied the Rab family small GTPase Ypt1p, which exhibits a stress-driven structural and functional switch from a GTPase to a molecular chaperone, and mediates thermotolerance in Saccharomyces cerevisiae . Gambarte Tudela et al [ 25 ] investigated the intracellular distributions and functions of Rab39a and Rab39b isoforms and showed different subcellular distributions and functions in lipid transport.…”
mentioning
confidence: 99%